2018
DOI: 10.1042/bsr20180738
|View full text |Cite|
|
Sign up to set email alerts
|

Casticin inhibits breast cancer cell migration and invasion by down-regulation of PI3K/Akt signaling pathway

Abstract: Casticin is one of the major active components isolated from Fructus viticis. Increasing studies have revealed that casticin has potential anticancer activity in various cancer cells, but its effects on breast cancer cell migration and invasion are still not well known. Therefore, the ability of cell migration and invasion in the breast cancer MDA-MB-231 and 4T1 cells treated by casticin was investigated. The results indicated that casticin significantly inhibited cell migration and invasion in the cells expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 47 publications
2
8
0
1
Order By: Relevance
“…The results of the present study showed that MTH-3 inhibits MDA-MB-231 cell invasion and migration by decreasing the activity of MMP-9, instead of that of MMP-2. These results were consistent with those reported by Fan et al (43), who demonstrated that casticin inhibits MMP-9 protein expression and activity in breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…The results of the present study showed that MTH-3 inhibits MDA-MB-231 cell invasion and migration by decreasing the activity of MMP-9, instead of that of MMP-2. These results were consistent with those reported by Fan et al (43), who demonstrated that casticin inhibits MMP-9 protein expression and activity in breast cancer cells.…”
Section: Discussionsupporting
confidence: 93%
“…And based on the finding, we explored the possible mechanism in several ways, such as inflammation-related signaling pathway and early response genes. The c-fos and c-jun signaling pathway has been studied for many years of their role in the cell migration [16,17]. In the present study, we found that scratching caused increased protein expression levels of these two proteins, which could be inhibited by the berberine treatment.…”
Section: Discussionsupporting
confidence: 57%
“…Breast cancer is the most prevalent type of cancer in women and is a major cause of mortality worldwide due to its poor prognosis and diagnostic procedures [49][50][51][52]. Pretreatment of casticin on MDA-MB-231 and 4T1 cells resulted in downregulation of MMP-9 mRNA protein expression but has no significant effect on MMP-2, suggesting that casticin can suppress both migration and invasion abilities in breast cancer cells.…”
Section: Casticin and Breast Cancermentioning
confidence: 99%